Eradication of Pinworms (Syphacia spp.) in a Laboratory Rodent Colony (Journal of Laboratory Animal Science, 2019)
Laboratory rodent colonies are commonly infested with pinworms namely Syphacia obvelata and Syphacia  muris, often results in clinical signs such as diarrhea and rectal prolapse in heavy infestation. The pinworm  infestation in rodents affects the experimental observations and hence it is important to eradicate them from the  colony. Division of Laboratory Animals at Sree Chitra Tirunal Institute for Medical Sciences and Technology  (SCTIMST) maintains rats and mice colonies. Pinworm ova were determined by perianal impression with  cellophane tape testing (CTT) under low power of a compound microscope. The mice and rats were divided  into 2 groups with 10 males and 10 females in each group. Group I was treated with piperazine (10.8 mg/ml of  drinking water) for a period of 28 days and group II was treated with piperazine (10.8 mg/ml) for a period of  14 days followed by ivermectin (0.01mg/ml) for 14 days. Cages and accessory equipments were disinfected  with activated gluteraldehyde, 2.45% w/v. All supplies including bedding and accessories were autoclaved  at 121oC temperature, 15 lb pressure for 20 minutes. The present study revealed that the parasites were  eradicated from those groups treated with combination drug (piperazine and ivermectin) therapy while the  group treated with piperazine alone could not demonstrate a complete eradication. The two drug (piperazine  and ivermectin) regime over a 4-week period, associated with appropriate sanitation programme was found to  be effective in eradication of pin worms in laboratory rodents.
Keywords: Syphacia muris; Syphacia murispiperazine; ivermectin